Exploring Students’ Perspectives on Procedure Text-Based Activities for Enhancing English Speaking Skills: A Descriptive Qualitative Study - Darmaida Sari (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Speaking is one of the English skills that many EFL students still find difficult, especially those who do not major in English. This study examines how students at the Faculty of Islamic Economics and Business, Institut Syekh Abdul Halim Hasan Binjai, perceive the use of procedure text in speaking instruction. A descriptive qualitative approach was applied, involving 15 students selected through purposive sampling. Data were gathered through semi-structured interviews and analyzed using data condensation, data display, and conclusion drawing. Most participants viewed the use of procedure text positively. They felt that its clear sequence helped them arrange ideas before speaking, making it easier to explain a process in a logical order. Several students also reported feeling more confident and becoming more involved during speaking activities because they had a structured guide to follow. At the same time, they acknowledged that limited vocabulary, pronunciation problems, and nervousness still affected their speaking performance. The findings suggest that procedure text provides practical support for speaking instruction, particularly for non-English major students. It offers opportunities to practice speaking in a more organized way while gradually building confidence and improving communicative ability in English.